Análise da convecção forçada laminar em dutos circulares submetidos aos efeitos da condução axial e radiação - Veloso, Dhiego Luiz de Andrade (2015)
With the great technological advances experienced by humanity becomes providential depth knowledge about real processes of heat transfer, as well as a need arises to analyze them quantitatively. In the present work is studied the heat transfer in laminar forced convective in the entrance region of a circular tube considering the effects of axial conduction into the fluid and radiation, since in low Peclet numbers play an important role in heat transfer problems and its omission offers a significant error in the computation of the heat transfer rate. In the first part of this work is considered a slug-flow, whose exact analytical solution was discussed. In the second part of the work is considered a flow in the power law model, proposes an approximate analytic solution and numerical solution, as well as the comparison of these solutions. In this paper is used the hybrid numericanalytical method named Generalized Integral Transform Technique (GITT) to solve the energy equation. The temperature field and local Nusselt number are calculated for several values of Peclet numbers and with a boundary condition of first kind. The results presented in the form of tables and graphs permit to analyze the influence that the Peclet number and the power law index exercise in the temperature profile and the Nusselt number. The results of this study are presented in full compliance with the scientific literature.